2016
DOI: 10.1002/pa.1596
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of the UN Global Compact in Spanish banking: a case study

Abstract: The aim of this work is to analyse the process involving adoption of a corporate social responsibility initiative-the United Nations Global Compact-in a Spanish financial institution. Semi-structured interviews were conducted for such purpose with managers, workers and customers from this organisation. From the analysis carried out, it can be ascertained that only professionals from the specific field of corporate social responsibility in the organisation being analysed have suitable knowledge about the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Bluewashing describes a smokescreen of practices used for purposes of public relations (Berliner & Prakash, 2015; Rasche, 2009). Very few empirical studies have analyzed such activities (Garayar et al, 2016; Macellari et al, 2021), and most research has focused on non‐empirical reflection on the business case for SDGs. For example, Bebbington and Unerman (2018) pointed out that SDGs could be used “to camouflage business‐as‐usual by disguising it using SDG‐related sustainability rhetoric” (p. 10).…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bluewashing describes a smokescreen of practices used for purposes of public relations (Berliner & Prakash, 2015; Rasche, 2009). Very few empirical studies have analyzed such activities (Garayar et al, 2016; Macellari et al, 2021), and most research has focused on non‐empirical reflection on the business case for SDGs. For example, Bebbington and Unerman (2018) pointed out that SDGs could be used “to camouflage business‐as‐usual by disguising it using SDG‐related sustainability rhetoric” (p. 10).…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…Like the SDGs, these initiatives had their own momentum. For example, the UNGC attracted very optimistic attention in both the practitioner and scholarly literature (e.g., Kell, 2005; Williams, 2004), but it was also associated with the phenomenon of bluewashing (e.g., Berliner & Prakash, 2015; Garayar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these reported positive outcomes of the UN GC, it is not completely free of criticism. For example, some NGOs express concerns that firms will draw upon the legitimacy of the UN without making significant progress in unfair business practices [4], namely "blue washing" [9,38] or "ceremonial adoption" [49], in the language of institutional theory. Berliner and Prakash [50] indicated that members of the UN GC showed worse performance on issues of environment and human rights which entail high costs.…”
Section: Un Global Compactmentioning
confidence: 99%
“…Hemphill (2005) defined UNGC as the world’s largest network-based voluntary corporate citizenship initiative as, by adhering, companies can show their commitment to meet the responsibilities requested by stakeholders (Néron and Norman, 2008). The improvement of firms’ image is one of the main benefits attributed to the UNGC (Arevalo and Aravind, 2017; Cetindamar, 2007; Garayar et al , 2016). It enables participants to exploit the recognised standing of the UN logo (Hughes and Wilkinson, 2001; Fritsch, 2008) and thus increase their reputation (Selvik, 2013).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%